PNG's rocky route to self-regulation - Luke Sela (Asia Pacific Network, 2000)
'Although we are not properly constituted, the Government does listen to us. We have actually issued our first edict— telling the advertising agencies what to do and when to say it. It is rather an interesting concept.'